What is the matter with Corbicula fluminea (Mollusca: Bivalvia: Cyrenidiae)? Occurrence of unusual shell erosion in Northern Italy. Issue 41 (10th November 2018) - Paganelli, Daniele; Sapienza, Giampiero; Sconfietti, Renato
ABSTRACT: Corbicula fluminea is a bivalve considered to be among the 100 worst invasive species in Europe due to its economic and ecological impacts in freshwater ecosystems. Here, we report for the first time a phenomenon of shell erosion observed in two distinct populations of C. fluminea collected in 2015 from two semi-natural small streams of the River Ticino hydrographic basin (Northern Italy). We measured several biometric variables in order to quantify the shell damage: length and thickness of the right valve and the shell free dry weight of each specimen and compared results with those of 'normal' populations from another stream of the same area. Our results confirmed that there was abnormal shell erosion and a reduction in shell thickness in both populations. We hypothesised several potential causes for the observed erosion, but none of them could provide sufficient explanation: neither the pH of the water, nor the level of calcium or total hardness of the water or granulometry of the substrates differed among streams. Similarly, predation pressure cannot be considered a reasonable explanation, since in the study area only a few animals actively prey on these bivalves and the marks they leave on the shells are completely different from the ones observed on our specimens. Lastly, we hypothesised that the bivalves may have been affected by a disease or parasitic infestation that had weakened their shells or prevented them from self-repairing and identified a fungal parasite that could possibly cause a disease to C. fluminea, namely the Ascomycota Geotrichum candidum . However, this species occurred only in one of the two abnormally eroded populations. In conclusion, a valid explanation for the morphological alteration that our study revealed has yet to be found.